Clinical characteristics and epidemiological situation of dengue fever in Peru: A systematic review. - Ledesma Negreiros, Gina Carmela (2024)
Introduction: Dengue is currently a concern in our country. Therefore, the aim of this study is to describe in detail the clinical characteristics and epidemiological situation of dengue in Peru. Methodology: Studies reporting patients with dengue fever in different regions of our country were identified and qualitatively summarized. The protocol of this investigation was registered in the Prospective International Register of Systematic Reviews (PROSPERO) database under the number CRD42024513895. An advanced search was conducted until February 18, 2024, in six databases, including PubMed, Scopus, Embase, Web of Science, Virtual Health Library, and Scielo. Observational studies and case reports were included. The results of the included articles were presented in tables and graphs. Results: The search results identified 545 articles, of which, after a rigorous selection process based on established criteria, 17 published between 1993 and 2023 were included. These studies covered 10 regions of Peru and included a total of 2310 patients diagnosed with dengue. Of the total, 43.68% (n = 1009) were female and 37.14% (n = 858) were male. Among the manifestations most frequently reported by patients were malaise, fever, headache, arthralgia, myalgia, retroocular pain, back pain, and rash/exanthema. In terms of outcome, the vast majority of patients managed to recover, while an unfortunate 1.73% (n = 40) died. Conclusions: The results presented provide a comprehensive view of the epidemiology of dengue and its clinical features in our country. These findings underline the urgent need to implement effective prevention and control strategies for this disease.